2D Catalytic, Chemodynamic, and Ferroptotic Vermiculite Nanomedicine. (11th October 2022) - Ma, Lifang; Huang, Hui; Feng, Wei; Chen, Liang; Xia, Lili; Yu, Yongchun; Wang, Jiayi; Chen, Yu
Abstract: The emerging chemodynamic therapy employs an iron‐based catalytic Fenton reaction to transform less‐reactive endogenous hydrogen peroxide within the tumor microenvironment (TME) into a highly toxic hydroxyl radical for killing cancer cells. However, the effective deployment of chemodynamic modality remains challenging, mired by a paucity of Fenton agents and overexpressed antioxidant glutathione (GSH) in cancer cells. Herein, a clay‐based 2D vermiculite nanosheet as a self‐reinforcing chemodynamic nanoagent for efficient lung cancer treatment is engineered. The engineered 2D vermiculite nanosheets are not only biocompatible with normal cells but also capable of regulating the TME through depleting GSH, which ameliorates the antioxidant activity of cancer cells. Meanwhile, GSH consumption results in increased intracellular reactive oxygen species content and enhanced lipid peroxidation level, thus inducing ferroptosis and augmenting chemodynamic cell‐killing efficacy. In particular, the ferrous oxidase hephaestin is the direct therapeutic target for 2D vermiculite nanosheets to fight against lung cancer cells. Systematic in vivo evaluations on a xenografted tumor model verify the favorable biosafety and effective tumor suppression capacity of the engineered 2D vermiculite nanosheets‐mediated chemodynamic tumor therapy by inducing desirable ferroptosis. Therefore, the developed vermiculite nanosheets represent the paradigm of 2D ferroptosis‐inducing nanomedicine for synergistic and efficient cancer treatment. Abstract : The clay‐based 2D vermiculite nanosheets are developed as a self‐reinforcing chemodynamic nanoagent for efficient lung cancer treatment by targeting ferroptosis through depleting glutathione and upregulating lipid peroxidation levels. The ferrous oxidase hephaestin is the direct therapeutic target for 2D vermiculite nanosheets to fight against lung cancer cells which is also demonstrated. This therapeutic modality presents a multifunctional nanoplatform for ferroptosis‐based cancer chemodynamic therapy.